From farm to table: Exploring food handling and hygiene practices of meat and milk value chain actors in Ethiopia - Nyokabi, N.S.; Phelan, L.; Gemechu, G.; Berg, S.; Lindahl, Johanna F.; Mihret, A.; Wood, J.L.N.; Moore, H.L. (Springer, 2023)
Livestock value chains constitute a source of livelihood for meat and milk value chain actors in Ethiopia, from dairy farmers to other associated value chain actors such as milk traders, abattoir workers, public health officials, veterinarians, butcheries selling meats, milk cooperatives, artisanal milk processors, and transporters. The development of these livestock value chains, however, is constrained by poor food safety and quality, while consumers are also exposed to public health risks due to milk and meat value chain actors’ food handling and hygiene practices.